Students’ Perception on Tandem: Language Exchange Application As a Learning Media to Improve Speaking Skills - Nurul Mifta Lubis; Emeliya Sukma Dara Damanik; Maryati Salmiah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The research that has been carried out is entitled "Students' Perception on Tandem: Language Exchange Application as a Learning Media to Improve Speaking Skills", which is based on the fact that learning English is not only seen from the way teachers teach but also seen from students' perceptions. Nowadays, English language learning has been followed by technological developments, especially in the use of learning media. With the presence of applications as English learning media, it helps students overcome problems and improves students' English speaking skills. The research methodology uses qualitative methods. The research participants were five students in the eighth semester majoring in English Education at the State Islamic University of North Sumatera. The technique for collecting participants was purposive sampling. From these results, the participants who have been obtained will be interviewed by writer. The data collection techniques used by researcher were questionnaires and in-depth interviews. And analyzed using qualitative data analysis. The results obtained reveal that (1) The Tandem application can be used as a tool to improve speaking skills, (2) Call & video call features are most helpful in improving speaking skills, and (3) The Tandem application is the most effective application for improving speaking skills. Based on the research findings above, students expressed positive perceptions regarding the use of the Tandem application as a learning media in improving students' speaking skills. The Tandem application improves students' speaking skills.